Cultivating Hadhrami Memory: The Politics of Haul in a Malay-Speaking Hadhrami Sultanate in Indonesia - Taufik, Egi Tanadi; Rijal, Syamsul (Universitas Islam Internasional Indonesia, 2024)
This article identifies haul, an annual commemoration of the death of charismatic figures, in Indonesia as political. The politicization of haul has been accompanied by a proliferation of narratives promoting the history of Hadhrami diaspora while strengthening the relationship between local Hadhramis and the local statesmen. This qualitative research examines the use of haul in Pontianak to commemorate selected syarif aristocrats. Pontianak, founded in the mid-eighteenth century by a syarif statesman, has a long-standing Hadhrami memory. Data for this study were collected through literature review, interviews, observation, and archival research related to Kadriah Sultanate’s haul events. The findings suggest that haul reshapes memories of the Kadriah Sultanate and Hadhrami identity for pragmatic purposes in local politics. By examining this case study of a commemorative religious event in the non-Arab world, it is shown that the local Arab sultanate redefines Hadhrami ethnic identity as nationalist, locally rooted, and heroic. Public haul festivals thus become effective tools for syarif politicians to exert influence in the religious and political spheres.